Physicochemical Characteristics of Groundwater Samples and Leachate from Gbagede Dumpsite, Amoyo, Kwara State, Nigeria - Yakubu, M.T.; Omar, S.A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2019)
This study determined the physicochemical properties of groundwater and leachate samples obtained from dumpsite at Gbagede, Amoyo in Kwara State, Nigeria. Water samples collected from two wells located at a distance of 15 m and 150 m from the dumpsite and leachate at Gbagede were analyzed for physical and chemical properties using standard methods. The turbidity of the groundwater samples (GW1 and GW2) and leachate was higher than the World Health Organization (WHO) Standard and Nigeria Standard Drink and Quality Water (NSDWQ) (Reference Standards). The conductivity, nitrate, nitrite, chloride, sulphate, dissolved oxygen, biochemical oxygen demand, zinc, copper, aluminum and nickel of the three samples were generally lower than the Reference Standards while the total suspended solids was barely detected. The pH of the GW1 sample was within the Reference Standards whereas that of GW2 and leachate samples were higher than the WHO and NSDQW standards. The alkalinity of GW1 and GW2 was lower than the Reference Standards whereas that of leachate was higher than Reference Standards. Phosphate levels in the groundwater samples were lower whereas in the leachate, it was higher than the Reference Standards. The chemical oxygen demand was lower in GW1 and GW2 whereas it was higher than the WHO recommended limit in the leachates. Lead content in GW1 and GW2 was lower whereas in the leachate, it was higher than WHO standard. The cadmium content in GW1 was within the Reference Standards; cadmium content in GW2 was lower than that of the Reference Standards whereas it was higher than the Reference Standards in the leachates. In conclusion, the open dumpsite at Gbagede have minimally impacted (5% of the physicochemical characteristics exceeded the reference limit) on the physicochemical characteristics of the ground water whereas the dumpsite had more impact (53% of the physiochemical characteristics) on the physiochemical characteristics of the leachate.